The Spanish Version of the Functional Rating Index in Patients With Low Back Pain: Preliminary Results of the Validation Study - Medina-Porqueres, Iván; Torres-Fernandez, Manuel; Palenque-Lobato, Francisco Javier; Poljakovic-Kovacev, Nina; Bellido-Da-Conceiçao, Antonio; Feise, Ron J.; Cantero-Téllez, Raquel (Elsevier, 2019)
Objective: To assess the reliability, validity, and the psychometric properties of the Spanish version of the Functional Rating Index (Sp-FRI) in a preliminary cohort of patients with low back pain (LBP). Design: Prospective observational multicenter study. Setting: Outpatient physical therapy clinics and units from public and private settings. Participants: Patients with LBP (NZ22; 52.5 12.5y) entered the study. Interventions: The translation and cross-cultural adaptation were performed following inter- national guidelines through a 5-step procedure. Main Outcome Measures: The Sp-FRI was administered along with the Spanish version of Roland-Morris Disability Questionnaire (Sp-RMDQ) and numeric pain rating scale (NPRS) index. Preliminary testing included readability, comprehensibility, ceiling and floor effects, reliability, and validity. Statistical analysis was based on the Fernandez-Huerta index, and the calculation of Cronbach alpha, intraclass correlation coefficient (ICC), and Spearman s
Keywords: Lumbalgia - Fisioterapia; Cross-cultural comparison; Funtional rating index; Low back pain; Psychometrics; Rehabilitation; Translations